Skeletal Animation Based on BVH Motion Data - Huan Dai; Bo Cai; Jia Song; Dengyi Zhang (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Skeletal animation model is widely used in character animation. But bounded actions lead to the complexity of making animation data and lower reuse. BVH file, as a universal human feature animation file formats, is popular because of its wide source and making-easy. This paper presented a method by using BVH file as the animation data, to drive the skeletal animation. Based on the analysis of BVH file structure, this paper establishes data structure to parse the BVH file, and also designs a recursive parsing algorithm. At last, we implement the diversification of skeletal animation model of mesh by accessing BVH motion data to drive the skeletal animation The experimental results show that our method is accuracy and efficient.